2016
DOI: 10.1002/ldr.2644
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Cyanobacterial Diversity in Response to Agricultural Soils Associated with Dust Emission

Abstract: Dust emission to the atmosphere from wind‐eroded soils has many environmental impacts, including soil degradation and air pollution. Various agricultural land uses alter the topsoil properties and thus affect dust particle characteristics as well as loading of biological components into the air. In the present work, the richness and abundance of bacterial communities in topsoils of semiarid loess that are associated with dust emissions were studied by high throughput sequencing methods and were found to be aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…52 The relative abundance of Proteobacteria was also shown to increase in agricultural Negev soils. 54 Moreover, the abundance of γproteobacteria increased in N-amended soils. 55 Collectively, these data support the notion that fertilized agricultural soil microbiomes harbor more active, r-strategist (copiotrophic) We therefore suggest that the increasing influence of the local dust microbiome was related to the observed change in wind direction on the last day of the Saudi Arabian storm (Table 3).…”
Section: ■ Experimental Sectionmentioning
confidence: 98%
See 1 more Smart Citation
“…52 The relative abundance of Proteobacteria was also shown to increase in agricultural Negev soils. 54 Moreover, the abundance of γproteobacteria increased in N-amended soils. 55 Collectively, these data support the notion that fertilized agricultural soil microbiomes harbor more active, r-strategist (copiotrophic) We therefore suggest that the increasing influence of the local dust microbiome was related to the observed change in wind direction on the last day of the Saudi Arabian storm (Table 3).…”
Section: ■ Experimental Sectionmentioning
confidence: 98%
“…51,52 Previous studies have demonstrated that in Egyptian and Negev desert soils that were claimed for agriculture, the relative abundance of this phylum decreased, while that of Firmicutes increased, compared with pristine non-agricultural desert soils. 53,54 Firmicutes have also been shown to be negatively correlated with the precipitation gradient in Israel, exhibiting an increased relative abundance in arid and semiarid Negev soils compared with soils under Mediterranean climate. 52 The relative abundance of Proteobacteria was also shown to increase in agricultural Negev soils.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Its loamy texture is composed mostly of silt and clay particles (<50 µm), but also of fine to medium sand particles (50-200 µm). In recent years, the loess soils in the northern Negev have been subjected to the strain of increased human pressure and dust emission [28].…”
Section: The Experimental Soilsmentioning
confidence: 99%
“…Total of 423,762 bacterial sequence reads were recovered and subjected to the software package QIIME, leaving a total of 388,217 bacterial reads after chimeric and primer sequences removal and 14,411–25,613 bacterial reads for each sample. Sequence data were clustered into operational taxonomic units (OTU) at 97% similarity and classified with the nonredundant Greengenes reference OTU build (version 13.8; 97% similarity database; 99,322 sequences [ Katra et al ., ].…”
Section: Methodsmentioning
confidence: 99%